Cellulose Nanocrystal Elastomers with Reversible Visible Color. Issue 1 (4th December 2019) - Boott, Charlotte E.; Tran, Andy; Hamad, Wadood Y.; MacLachlan, Mark J.
Abstract: Responsive photonic crystals have potential applications in mechanical sensors and soft displays; however, new materials are constantly desired to provide new innovations and improve on existing technologies. To address this, we report stretchable chiral nematic cellulose nanocrystal (CNC) elastomer composites that exhibit reversible visible color upon the application of mechanical stress. When stretched (or compressed) the colorless materials maintain their chiral nematic structure but the helical pitch is reduced into the visible region, resulting in coloration of the CNC‐elastomer composite. By increasing the percentage elongation of the material (ca. 50–300 %), the structural color can be tuned from red to blue. The color of the materials was characterized by reflectance optical microscopy and reflectance circular dichroism to confirm the wavelength and polarization of the reflected light. We also probed the mechanism of the structural color using 2D‐X‐ray diffraction. Finally, by either water‐patterning the starting CNC film, or by forming a CNC film with gradient color, through masked evaporation, we were able to prepare encoded stretchable chiral nematic CNC‐elastomers. Abstract : Mechanical stress sensors were prepared from cellulose nanocrystal‐elastomer composites, which provide a reversible visible color readout.